Management of patients with patent foramen ovale and cryptogenic stroke: A collaborative, multidisciplinary, position paper. Issue 1 (8th April 2013) - Pristipino, Christian; Anzola, Gian Paolo; Ballerini, Luigi; Bartorelli, Antonio; Cecconi, Moreno; Chessa, Massimo; Donti, Andrea; Gaspardone, Achille; Neri, Giuseppe; Onorato, Eustaquio; Palareti, Gualtiero; Rakar, Serena; et al.
<x xml:space="preserve">Abstract</x> Objectives: To organize a common approach on the management of patent foramen ovale (PFO) and cryptogenic stroke that may be shared by different specialists. Background: The management of PFO related to cryptogenic stroke is controversial, despite an increase in interventional closure procedures. Methods: A consensus statement was developed by approaching Italian national cardiological, neurological, and hematological scientific societies. Task force members were identified by the president and/or the boards of each relevant scientific society or working group, as appropriate. Drafts were outlined by specific task force working groups. To obtain a widespread consensus, these drafts were merged and distributed to the scientific societies for local evaluation and revision by as many experts as possible. The ensuing final draft, merging all the revisions, was reviewed by the task force and finally approved by scientific societies. Results: Definitions of transient ischemic attack and both symptomatic and asymptomatic cryptogenic strokes were specified. A diagnostic workout was identified for patients with candidate event(s) and patient foramen ovale to define the probable pathogenesis of clinical events and to describe individual PFO characteristics. Further recommendations were provided regarding medical and interventional therapy considering individual risk factors of recurrence. Finally, follow‐up evaluation was appraised. Conclusions: Available data provided the basis for a shared approach to management of cryptogenic ischemic cerebral events and PFO among different Italian scientific societies. Wider international initiatives on the topic are awaited. © 2013 Wiley Periodicals, Inc.